1997
DOI: 10.1177/001789699705600207
|View full text |Cite
|
Sign up to set email alerts
|

Breakthrough or bandwagon? Are interventions tailored to Stage of Change more effective than non-staged interventions?

Abstract: There has been considerable interest in the application of the Stages of Change model developed by Prochaska and DiClemente. Much ha s b e e n written about the model's implications for lifestyle change interventions, and national training programmes are underway to train health care staff to provide brief stage-specific interventions. However, the r e i s , as yet, relatively little evidence comparing stage-based with non-stage-based interventions. It is argued from this review of the evidence that it is diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
28
0
2

Year Published

1998
1998
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 18 publications
0
28
0
2
Order By: Relevance
“…It is possible to develop different interventions for each of the five stages (Ashworth, 1997). Tailoring nutrition counselling to the stages of change has been suggested to increase programme effectiveness (Ashworth, 1997;Kristal et al, 1999;Steptoe et al, 1999Steptoe et al, , 2001.…”
Section: The Stages Of Change Model For Nutrition Counsellingmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible to develop different interventions for each of the five stages (Ashworth, 1997). Tailoring nutrition counselling to the stages of change has been suggested to increase programme effectiveness (Ashworth, 1997;Kristal et al, 1999;Steptoe et al, 1999Steptoe et al, , 2001.…”
Section: The Stages Of Change Model For Nutrition Counsellingmentioning
confidence: 99%
“…Tailoring nutrition counselling to the stages of change has been suggested to increase programme effectiveness (Ashworth, 1997;Kristal et al, 1999;Steptoe et al, 1999Steptoe et al, , 2001. Although some studies have shown favourable results of stage-matched nutrition counselling (Campbell et al, 1994;Steptoe et al, 1999Steptoe et al, , 2001Tilley et al, 1999;Van der Veen et al, 2002), the principle of stage-matched approaches in nutrition counselling is not undisputed.…”
Section: The Stages Of Change Model For Nutrition Counsellingmentioning
confidence: 99%
“…6 Although the TTM was originally developed to explain smoking cessation behaviour, its application to the uptake of physical activity has been confirmed. 7 8 This, and its success in helping people change other unhealthy behaviours, particularly smoking, 9 has led to recommendations for its use in activity promotion. 6 10 This paper critically reviews published reports of TTM based, activity promotion interventions and attempts to answer the question: is there evidence of an additional effect of TTM based activity promotion interventions over non-staged interventions?…”
mentioning
confidence: 99%
“…The TTM has been used to design interventions to promote positive behaviours such as physical activity/exercise (Adams and White, 2003;Spencer et al, 2006), healthy eating (Armitage et al, 2004;Horwath, 1999;Spencer et al, 2007), and mammography screening (Ashworth, 1997;Spencer, Pagell, and Adams, 2005), as well as to help people avoid pregnancy and sexuallytransmitted diseases (Horowitz, 2003) and overcome harmful behaviours such as smoking and substance abuse (Migneault, Adams, and Read, 2005;Spencer et al, 2002). The apparent success of some of these communication and intervention programmes suggests that it might be worth applying insights from the model to the promotion of lower-carbon and other sustainability-related behaviours.…”
Section: Applications and Criticismsmentioning
confidence: 99%
“…However, researchers suggest that many studies are poorly designed, and stage-based interventions often fail to represent accurately all facets of the TTM (Ashworth, 1997;Bridle et al, 2005;Hutchison, Breckon, and Johnston, 2009). …”
Section: Applications and Criticismsmentioning
confidence: 99%